Experimental study on mechanical properties of hemp fibers influenced by various parameters - Ribeiro, J.E. (2023)
Hemp fibers produced by different extraction techniques that were cultivated in the Portuguese districts of Braganca and Mirandela under various nitrogen fertilization and planting density conditions are examined and mechanically described in this paper. The objective of this study is to evaluate the influence of sowing density, nitrogen fertilization, sample location, and extraction method in order to improve the mechanical properties of hemp fibers. To achieve this, we determined the modulus of elasticity, the tensile strength, and the density. The mean value for the modulus of elasticity was 92.44 & PLUSMN; 7.44 GPa, the mean of tensile strength was 564.98 & PLUSMN; 167.03 MPa, and the mean of the density was 1.64 & PLUSMN; 0.24 g cm(-3). We performed a statistical analysis of all parameters using ANOVA and found that the retting method had the greatest influence among all parameters. The associated effects of nitrogen fertilization and sowing density revealed an important influence on tensile strength and specific tensile strength, respectively.